Tuesday

March 3, 2015

March 3, 2015

Posted by **noel** on Thursday, May 24, 2012 at 10:00pm.

a. f(x) = 1/x-2 + 3

b. f(x) = 2(x – 4)^2 + 5

- math -
**Steve**, Friday, May 25, 2012 at 12:27amy = 1/(x-2) + 3

y-3 = 1/(x-2)

x-2 = 1/(y-3)

x = 1/(y-3) + 2

so, f^{-1}(x) = 1/(x-3) + 2

y = 2(x-4)^2 + 5

y-5 = 2(x-4)^2

(y-5)/2 = (x-4)^2

now, we can use ± root, so let's choose the + root:

√[(y-5)/2] = x-4

√[(y-5)/2]+4 = x

so, f^{-1}(x) = √[(x-5)/2] + 4

**Answer this Question**

**Related Questions**

Math - Let R1 be a binary relation on the set of integers defined as follows: R1...

Math Questions - 1.) What is the inverse of the relation (3, -1), (2. 5), (-4, -...

Math - 1.) What is the inverse of the relation (3, -1), (2. 5), (-4, -4)? 2.) ...

Math - Given f(x)=7-2(x-1)^2, x>= 1, determine f inverse (5).

Math - Given f(x)=7-2(x-1)^2, x>= 1, determine f inverse (5).

algebra - Determine whether the following relation represents a function. If the...

Math - Given f(x)=2x^2-1, determine the equation of the inverse.

HELP!!! Math - Given the relation A = {(5,2),(7,4),(9,10),(x,5)}. What is the ...

math - Determine the inverse of f(x)=(x^3)-2 Is the inverse the switch of ...

math - indicates required items An operation * is defined by the relation x*y = ...